Correlate of business incubators and small medium and micro-enterprises development (SMMEs) in Nigeria - Popoola, Mufutau Akanmu; Ojo, Azeez Olasunkanmi; Akintunde, Mutairu Oyewale (Management and Entrepreneurship: Trends of Development, 2024)
This research explored the effect of business incubators on Small, Medium and Micro-enterprises (SMMEs). The objectives of the study were to assess the significant relationship between business incubators and Small, Medium and Micro-enterprises (SMMEs) and also to determine the significant relationship betweenentrepreneurs’views and business incubation.60 incubatees was the population of the study which comprised of Ogun and Lagos State National Board of Technological Beneficiaries (NBTI). The research instrument was questionnaire. The ex-post facto method and Yamane formula was employed. Analysis of variance (ANOVA) and correlation efficient was adopted. The responds gotten from the questionnaire was be sorted, coded and the statistical Packages for Social Sciences (SPSS) version 20.0 was employed. The empirical findings revealed that there is a significant relationship between business incubators and Small, Medium and Micro-enterprises (SMMEs) development. The findings of hypothesis two show that there is a significant relationship between Business Incubation Program and Entrepreneurs view. The study found out that fear of failure of business has reduced as a result of business incubation which has benefited startup ventures. It has been reveled in this study that business incubation increases the numbers of startup ventures. The study recommends that Entrepreneurs must make sure they participate in incubation programs to enhance their knowledge acquisition and skills through training and development which will reduces business failure. JEL Classification: М13, М20, М21